Researcher Perspectives on Data Sharing in Deep Brain Stimulation - Zuk, Peter; Sanchez, Clarissa E.; Kostick, Kristin; Torgerson, Laura; Muñoz, Katrina A.; Hsu, Rebecca; Kalwani, Lavina; Sierra-Mercado, Demetrio; Robinson, Jill O.; Outram, Simon; Koenig, Barbara A.; Pereira, Stacey; et al. (Frontiers in Human Neuroscience, 2020)
The expansion of research on deep brain stimulation (DBS) and adaptive DBS (aDBS) raises important neuroethics and policy questions related to data sharing. However, there has been little empirical research on the perspectives of experts developing these technologies. We conducted semi-structured, open-ended interviews with aDBS researchers regarding their data sharing practices and their perspectives on ethical and policy issues related to sharing. Researchers expressed support for and a commitment to sharing, with most saying that they were either sharing their data or would share in the future and that doing so was important for advancing the field. Those sharing also reported a variety of sharing partners, however, suggesting a lack of uniform sharing practices in the field. Researchers described several concerns and barriers related to sharing, including privacy and confidentiality, usability of shared data by others, ownership and control of data (including potential commercialization), and limited resources for sharing. They also suggested potential solutions to these challenges, including additional safeguards to address privacy issues, standardization and transparency in analysis to address issues of data usability, professional norms and heightened cooperation to address issues of ownership and control, and streamlining of data transmission to address resource limitations. Researchers also offered a range of views on the sensitivity of neural activity data and data related to mental health in the context of sharing. These findings are an important input to deliberations by researchers, policymakers, neuroethicists, and other stakeholders as they navigate ethics and policy questions related to aDBS research.